A tale of two nationalisations: experiences of post 1945 public ownership in the UK and France compared. (29th March 2019) - Cumbers, Andrew
As public ownership comes back into fashion following the failings and growing contradictions of neoliberal processes of marketisation and privatisation, it is important to learn the lessons for public policy from earlier processes of nationalisation. In this article, I compare the post 1945 experiences of nationalisation in the UK and France. Both countries underwent sweeping processes of nationalisation in the aftermath of the Second World War amidst a broader international shift towards a more state driven model of economic development under capitalism. However, the two experiences of nationalisation diverged considerably, reflecting underlying differences in past forms of economic development, the different balance of class forces and the integration of each country into the broader global economy. The article suggests that these experiences remind us of the importance of a variegated perspective on the evolution of capitalism, distinctive political-economic trajectories and situating major policy shifts in time and space.